Functional Food Targeting the Regulation of Obesity-Induced Inflammatory Responses and Pathologies. (25th May 2010) - Hirai, Shizuka; Takahashi, Nobuyuki; Goto, Tsuyoshi; Lin, Shan; Uemura, Taku; Yu, Rina; Kawada, Teruo
Abstract : Obesity is associated with a low-grade systemic chronic inflammatory state, characterized by the abnormal production of pro- and anti-inflammatory adipocytokines. It has been found that immune cells such as macrophages can infiltrate adipose tissue and are responsible for the majority of inflammatory cytokine production. Obesity-induced inflammation is considered a potential mechanism linking obesity to its related pathologies, such as insulin resistance, cardiovascular diseases, type-2 diabetes, and some immune disorders. Therefore, targeting obesity-related inflammatory components may be a useful strategy to prevent or ameliorate the development of such obesity-related diseases. It has been shown that several food components can modulate inflammatory responses in adipose tissue via various mechanisms, some of which are dependent on peroxisome proliferator-activated receptor γ (PPARγ ), whereas others are independent on PPARγ, by attenuating signals of nuclear factor-κ B (NF-κ B) and/or c-Jun amino-terminal kinase (JNK). In this review, we introduce the beneficial effects of anti-inflammatory phytochemicals that can help prevent obesity-induced inflammatory responses and pathologies.